Individualized acute kidney injury after care. Issue 6 (December 2020) - Koyner, Jay L.; Haines, Ryan W.; Bouchard, Josee
Abstract : Purpose of review: The aim of this study was to summarize the current evidence around the impact of individualizing patient care following an episode of acute kidney injury (AKI) in the ICU. Recent findings: Over the last years, evidence has demonstrated that the follow-up care after episodes of AKI is lacking and standardization of this process is likely needed. Although this is informed largely by large retrospective cohort studies, a few prospective observational trials have been performed. Medication reconciliation and patient/caregiver education are important tenants of follow-up care, regardless of the severity of AKI. There is evidence the initiation and/or reinstitution of renin-angiotensin-aldosterone agents may improve patient's outcomes following AKI, although they may increase the risk for adverse events, especially when reinitiated early. In addition, 3 months after an episode of AKI, serum creatinine and proteinuria evaluation may help identify patients who are likely to develop progressive chronic kidney disease over the ensuing 5 years. Lastly, there are emerging differences between those who do and do not require renal replacement therapy (RRT) for their AKI, which may require more frequent and intense follow-up in those needing RRT. Summary: Although large scale evidence-based guidelines are lacking, standardization of post-ICU-AKI is needed.